Development of informative support for automatic antisurge protection system and regulation of gas pumping plant - Семенцов, Георгій Никифорович; Давиденко, Лідія Ігорівна (Eastern-European Journal of Enterprise Technologies, 2014)
The article deals with the nature and advisability of further informative support for automatic antisurge protection system and regulation of gas pumping plant boosters of natural gas storage compressor station based on improved performance of existing antisurge control systems by applying the method of data fusion. The study was conducted at gas compressor unit № 9 (booster compressor station, natural gas storage "Bilche-Volytsya"). The analysis of the statistical characteristics of informative indicators as the rate of gas pressure increase: evaluation of mathematical expectation, variances, normalized autocorrelation function, spectral density, distribution law has been done. The autocorrelation function of the degree of gas pressure increase was analyzed too. The equation of the autocorrelation function was shown to have two components: the exponential and cosine ones. Amplitude and phase response of shaping filter for the degree of increase of gas pressure centrifugal blower gas-compressor unit was evaluated having done the analysis of experimental results. The advisability of the method of data fusion in automatic antisurge protection and regulatory systems was proved.